Effectiveness of yoga and educational intervention on disability, anxiety, depression, and pain in people with CLBP: A randomized controlled trial. (May 2018) - Kuvačić, Goran; Fratini, Patrizia; Padulo, Johnny; Antonio, Dello Iacono; De Giorgio, Andrea
Abstract: Objective: The current study investigates the effects of an 8-week yoga program with educational intervention compared with an informational pamphlet on disability, anxiety, depression, and pain, in people affected by chronic low back pain (CLBP). Methods: Thirty individuals (age 34.2 ± 4.52 yrs) with CLBP were randomly assigned into a Yoga Group (YG, n = 15) and a Pamphlet Group (PG, n = 15). The YG participated in an 8-week (2 days per week) yoga program which included education on spine anatomy/biomechanics and the management of CLBP. Main outcome measures: Monitoring response to intervention, the Oswestry Low Back Pain Disability Questionnaire (ODI-I), Zung self-Rating Depression Scale (SDS), Zung Self-Rating Anxiety Scale (SAS) and Numeric Rating Scale for Pain (NRS 0–10) were used to collect data. Results: After intervention, the YG showed a significant decrease (p < 0.05) in the mean score in all assessed variables when compared with baseline data. In addition, statistically significant (p < 0.05) differences were observed among groups at the end of intervention in depression, anxiety, and pain, but not in disability. Conclusions: The yoga program and education together appear to be effective in reducing depression and anxiety, which can affect perception of pain. Highlights: Yoga combined with education has a favorable psychological effects on individuals with CLBP. If patients are only told about what exercises to do for their illness, they will not be able to improve their QoL. Collaboration with health/training experts is crucial to patients' QoL.